Efek Pesan Membujuk Dalam Membentuk Niat Membeli Online: Studi Penggunaan Media Sosial Klinik Kecantikan di Kota Solo - Didik Setyawan (Media Akuntansi, 2019)
This study aims to examine the effects of social media in influencing intentions to online purchase. The phenomenon that occurs is still a gap between followers and the level of activity of each information posted on social media of beauty clinic in Surakarta. The method in this study used a sampling technique using purposive sampling wich the population are 210 respondents in Solo who use beauty clinic’s social media application. Hypothesis tested using Structural Equation modeling (SEM) with AMOS program. The result of this study shows all hypothesis supported except H5a, H6a and H6b. These results means that to form an intention to online purchase in the use of beauty clinic social media through perceived attitudes and values influenced by information credibility, source credibility, source attractiveness, and the perception of sources from the beauty clinic's social media.